Investigations of the causes of chatter in computer aided manufacturing process during end milling operation - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry; Alam, S. (2008)
Chatter is an unwanted but sometimes unavoidable phenomenon in computer aided machining. The term defines the self-excited violent relative dynamic motion between the cutting tool and workpiece. Experimental investigations have been conducted on the chips and common types of discreteness in the form of serrated saw teeth have been identified. It has been identified that the chip formation process has a discrete nature, associated with the periodic shearing process of the chip during machining of Ti6Al4V. Apart from the primary serrated teeth, a typical instability of periodic nature, in the form of secondary saw/serrated teeth, which appear at the free edge of the chip, has been identified. Mechanism of formation of these teeth has been studied and the frequency of their formation has been determined. The different modes of the vibrating components have been extracted by modal analysis and the vibration responses during cutting conditions have also been recorded using an online monitoring data acquisition system. The most vibrating components during computer aided milling machine operation have been identified. It has been found that chatter appears in the system as a resonance during cutting when the chip serration frequency is equal or any integer multiple of the prominent natural frequency of the system components like spindle, tool holder.